2004
DOI: 10.1007/s00436-004-1158-9
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of an integrin-like protein and protein kinase C in amoebic adhesion to fibronectin and amoebic cytotoxicity

Abstract: Adherence of a pathogen to the host cell is one of the critical steps in microbial infections. Naegleria fowleri, a causative agent of primary amoebic meningoencephalitis in humans, is expected to interact with extracellular components of the host, such as fibronectin, in a receptor-mediated mode. In this study, we investigated the interaction between N. fowleri and fibronectin to understand its cytopathology. In binding assays using immobilized fibronectin, the number of amoebae bound to fibronectin was incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 18 publications
4
36
0
1
Order By: Relevance
“…Species of Acanthamoeba have been reported to bind to laminin-1, collagen IV and fibronectin (Gordon et al, 1993 et al, 2001). Consistent with these observations, it has been reported that N. fowleri binds to immobilized fibronectin in a concentration-dependent manner through the mediation of a 60 kDa fibronectin-binding protein (Han et al, 2004).In the present study the binding and invasive properties of thermotolerant pathogenic N. fowleri were compared with those of a thermotolerant non-pathogenic species, Naegleria lovaniensis. Adhesion to ECM components was shown to differ between the two species, with a higher level of adhesion observed for N. fowleri.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…Species of Acanthamoeba have been reported to bind to laminin-1, collagen IV and fibronectin (Gordon et al, 1993 et al, 2001). Consistent with these observations, it has been reported that N. fowleri binds to immobilized fibronectin in a concentration-dependent manner through the mediation of a 60 kDa fibronectin-binding protein (Han et al, 2004).In the present study the binding and invasive properties of thermotolerant pathogenic N. fowleri were compared with those of a thermotolerant non-pathogenic species, Naegleria lovaniensis. Adhesion to ECM components was shown to differ between the two species, with a higher level of adhesion observed for N. fowleri.…”
supporting
confidence: 69%
“…It has been reported previously that protozoa that are pathogenic recognize components of the ECM (Gordon et al, 1993;Han et al, 2004;Rocha-Azevedo et al, 2007Shibayama et al, 2003). For example, Entamoeba histolytica binds to ECM components, an interaction that may play an important role in its penetration of the intestinal mucosa (de Lourdes Muñoz et al, 2001;Li et al, 1995; Talamás-Rohana & Meza, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…For many micro-organisms, adherence is one of the most important features observed during the early invasion of different tissues or organs (Kucknoor et al, 2005;McCoy et al, 1994;Panjwani, 2010). N. fowleri is known to adhere to different cell types in a process that involves glycoconjugates as well as extracellular matrix proteins, such as fibronectin and collagen (Cervantes-Sandoval et al, 2010;Han et al, 2004;Shibayama et al, 2003). During the initial adherence step, N. fowleri may activate intracellular signals that could be important for traversing epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…fowleri to bind to nasal mucosa, locomotion, and chemotactic response to nerve cell components play a substantial role in disease progression (68)(69)(70) …”
Section: Contact-dependent Mechansimsmentioning
confidence: 99%